2018
DOI: 10.1002/celc.201801105
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Electrochemical Stability and Lithium Ion‐Dominant Transport in Concentrated Poly(ethylene carbonate) Electrolyte

Abstract: Ion‐conductive solid polymer electrolytes (SPEs) are important materials for implementing safer energy storage. In the present study we show that a concentrated SPE composed of poly(ethylene carbonate) (PEC) and lithium bis(fluorosulfonyl)imide (LiFSI) has high oxidation tolerance and prevents aluminum corrosion. These properties enable cycling of a LiMn2O4 cell charged above 4 V. Battery operation above 4 V is difficult for conventional polyether electrolytes because of their poor electrochemical stability. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
(144 reference statements)
1
37
0
Order By: Relevance
“…In “polymer in salt” electrolytes, the enhanced oxidation stability and interface stability with Al foil are also reported by Y. Tominaga et al In concentrated PEC‐LiFSI electrolytes, they demonstrated the nearly saturated CO···Li + interaction and the aggregate FSI ions at high concentrations above 50 mol% through FTIR and Raman spectroscopy, respectively (Figure b) . Furthermore, to investigate the effect of concentration on the oxidation stability of PEC‐based electrolyte, they compared the linear sweep voltammograms of PEC‐LiFSI 10 and 120 mol% electrolytes, as shown in Figure c.…”
Section: High‐voltage Compatibility Of Polymer Electrolytesmentioning
confidence: 61%
See 2 more Smart Citations
“…In “polymer in salt” electrolytes, the enhanced oxidation stability and interface stability with Al foil are also reported by Y. Tominaga et al In concentrated PEC‐LiFSI electrolytes, they demonstrated the nearly saturated CO···Li + interaction and the aggregate FSI ions at high concentrations above 50 mol% through FTIR and Raman spectroscopy, respectively (Figure b) . Furthermore, to investigate the effect of concentration on the oxidation stability of PEC‐based electrolyte, they compared the linear sweep voltammograms of PEC‐LiFSI 10 and 120 mol% electrolytes, as shown in Figure c.…”
Section: High‐voltage Compatibility Of Polymer Electrolytesmentioning
confidence: 61%
“…The HOMO energy of LiTFSI (−10.19 eV) is much lower than that of LiFSI (about −7.5 eV) . The experimental results also demonstrate that the poly(trimethylene carbonate) (PTMC)‐LiTFSI has better antioxidant ability than that of PEC‐LiFSI . Nevertheless, due to the different measurement conditions between research groups, it is difficult to strictly compare the influence of salt type and concentration on stability.…”
Section: High‐voltage Compatibility Of Polymer Electrolytesmentioning
confidence: 98%
See 1 more Smart Citation
“…This is indicative of formation of salt agglomerates as previously reported by Tominaga et al for high-concentration poly(ethylene carbonate):LiFSI electrolytes. 31 This initially subtle shift in peak position undergoes a sudden jump between n = 3 and n = 2, i.e., at the previously suggested percolation threshold.…”
Section: Ion Coordinationmentioning
confidence: 79%
“…Tominaga and coworkers demonstrated that Li salt concentration and polymer structure have a significant influence on LITN of SPEs. [ 173–175 ] For example, more than 50 mol% lithium bis(fluorosulfonyl)imide (LiFSI) in PEC gives a high LITN of up to 0.6. This is because FSI anions tend to form aggregates, which have strong bonding with the CO group in PEC.…”
Section: Strategies To Improve Li+ Transference Numbermentioning
confidence: 99%